Pertimbangan Besaran Upah Minimum Kabupaten Banyumas OlehDewan Pengupahan Kabupaten Banyumas - haris kusuma wardana haris; Agoes Djatmiko; Wahyu Hariadi (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2024)
This paper is entitled Considerations of the Banyumas Regency Minimum Wage Amount by the Banyumas RegencyWage Council. This study aims to determine the process of implementing the Banyumas Regency minimum wage in2023. This research is a sociological juridical research with the subject of study by the Banyumas RegencyManpower, Cooperatives and SMEs Service. The aim of this research is to build synergy between the BanyumasRegency Wage Council and the obstacles in determining the minimum wage in Banyumas Regency. Wages areincome received by workers in the form of money, which includes not only wages/salaries, but also overtime andallowances received on a regular basis, excluding holiday allowances which are annual, quarterly, and otherallowances which are not routine. Wages are all kinds of payments arising from work contracts, regardless of thetype of work, which are a form of income received by workers as compensation for the work they do. To determinethe district minimum wage in accordance with community standards, the district minimum wage is determined bythe government, namely the district Department of Manpower, Cooperatives and Small and Medium Enterprises.Keywords: Wages, Wage Council, Banyumas Regency